The effect of financial risks on the performance of Islamic and commercial banks in UAE - Oudat, Mohammad Salem; Ali, Basel J. A.; Abdelhay, Sameh; Hazaimeh, Haziem M.; Altalay, Mohamed Saif Rashid; Marie, Attiea; El-Bannany, Magdi (Frontiers in Applied Mathematics and Statistics, 2024)
Risk management has emerged as a critical element across several economic sectors, with particular significance in the banking industry. The governing bodies of these industries encounter a multitude of threats stemming from the escalation of an unpredictable economic environment, the intricacy of transactions and big data, and several other concealed factors. The primary aim of the present research is to investigate the impact of certain financial risks, including capital risk, liquidity risk, and operational risk, on the financial performance of both commercial and Islamic banks operating within the banking sector of the United Arab Emirates. The study will focus on the time frame spanning from 2015 to 2022. The findings indicate that there is a statistically significant positive relationship between capital risk and both return on assets (ROA) and return on equity (ROE).